Albania : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper and Statistical Appendix paper examines the issue of dollarization in Albania against the background of rapidly evolving banking, policy and prudential systems, and of growing importance of monetary policy as a tool for demand management. The period covered is 1998-the immediate aftermath of the pyramid scheme collapse-to the present, which is a period of impressive, though gradual, transformation rather than of abrupt structural changes. The paper also analyzes the poverty situation in Albania, and discusses the poverty alleviation mechanisms that have worked.